Uterine low grade endometrial stromal sarcoma: a case report with review of literature - Devi, P. Urmila; Himaja, S.; Manasa, R.; Atla, Bhagya Lakshmi (International Journal of Research in Medical Sciences, 2017)
Endometrial stromal sarcomas are rare uterine tumours usually seen in perimenopausal females. We report here a case of low grade endometrial stromal sarcoma in a 45 year female with a clinical diagnosis of fibroid uterus and final histological diagnosis of low grade endometrial stromal sarcoma.